Pengaruh Arus Kas Operasi, Sales Growth dan Return On Assets Terhadap Financial Distress - Shobrina Al Alifah; Tumirin Tumirin (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This study aims to test and analyze the effect between operating cash flow, sales growth, and return on assets on financial distress in State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) for the period 2017 - 2021. The method of determining the sample in this study using purposive sampling. The collection method in this study uses secondary data, namely financial reports obtained from the Indonesia Stock Exchange (IDX). This study uses classic assumption test analysis tools, multiple linear regression analysis, T test, F test and coefficient of determination using the SPSS application. Partial research results show that operating cash flow, sales growth, and return on assets have a significant effect on financial distress. Simultaneous research results show that operating cash flow, sales growth, and return on assets have a significant effect on financial distress. Keywords: , , P, dan Return On Assets.